2018
DOI: 10.1186/s12883-018-1034-3
|View full text |Cite
|
Sign up to set email alerts
|

A survey of subjective constipation in Parkinson’s disease patients in shanghai and literature review

Abstract: BackgroundConstipation is one of the most frequent non-motor symptoms (NMS) in Parkinson’s disease (PD) and the prevalence of constipation in PD patients varies among different studies. We designed this study to survey the prevalence and clinical characteristics of subjective constipation and the appearance chronology between the emergence of constipation and onset of motor symptoms in PD patients from Shanghai, China.Methods268 PD patients were continuously recruited into this study. Parkinson’s related clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…The 24 h fecal water content is highly correlated to water intake in 6-OHDA rats treated with and without HM01. This finding is consistent with two clinical reports showing a reduction of liquid intake in PD patients associated with the incidence of constipation (Ueki and Otsuka, 2004; Gan et al, 2018). In addition, experimental evidence demonstrated that DA pathways from the midbrain to forebrain limbic system play a role in anticipatory and motivated drinking behavior (Cone et al, 2016; Hsu et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The 24 h fecal water content is highly correlated to water intake in 6-OHDA rats treated with and without HM01. This finding is consistent with two clinical reports showing a reduction of liquid intake in PD patients associated with the incidence of constipation (Ueki and Otsuka, 2004; Gan et al, 2018). In addition, experimental evidence demonstrated that DA pathways from the midbrain to forebrain limbic system play a role in anticipatory and motivated drinking behavior (Cone et al, 2016; Hsu et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…PD patients also showed reduced water intake compared to healthy controls (Ueki and Otsuka, 2004; Barichella et al, 2017). This adipsia is of potential relevance since two clinical surveys in PD patients pointed to an association between daily liquid intake and constipation (Ueki and Otsuka, 2004; Gan et al, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…They suggested that constipation and depression might share the mechanism related to 5-hydroxytryptamine (5-HT) depletion in the PD population 20 . Gan et al enrolled 268 PD patients and also reported significantly higher HAMD scores in PD with constipation (constipation versus non-constipation groups, HAMD scores 15.37 ± 11.38versus 12.05 ± 10.03; p = 0.019) 21 . In our study, we also observed a similar phenomenon, and it could be related to the pathway of α-syn propagation and involvement of important nuclei in brainstem, which leads to depression.…”
Section: Discussionmentioning
confidence: 97%
“…Constipation is defined as a frequency of less than three bowel movements in 1 week (56). Between 54 and 90% of PD patients suffer from constipation, and out of these, 48% report the onset of constipation up to 10 years prior to the onset of motor symptoms (20, 57, 58). Constipation is more frequent in patients with a rigid-bradykinetic phenotype and is related to the presence of neuropsychiatric symptoms, such as anxiety, depression, and insomnia (57).…”
Section: Specific Dysautonomic Symptoms In α-Synucleinopathiesmentioning
confidence: 99%